In-person vs. blended learning in post-COVID Colombia: impacts on children and adolescents’ mental health and quality of life - María Alejandra Palacios-Ariza; Johana Benavides-Cruz; Paula Andrea González-Amado; Julián Darío Sosa-Montañez; Janeth Consuelo Parra-García (International Journal of Adolescence and Youth)
COVID-19 disrupted global education, prompting use of blended learning. Its impact on children’s quality of life (HRQoL) in low- and middle-income settings remains unclear. We conducted a cross-sectional study of 270 students (ages 8–18) in Bogotá, Colombia, comparing HRQoL and mental health symptoms between blended and in-person learning groups using the KIDSCREEN-27 and WHO RQC questionnaires. No significant differences in HRQoL scores were found between learning modalities. Females reported lower HRQoL than males across several dimensions. Sleep issues, fear, and lack of interest in play were linked to lower HRQoL regardless of teaching method. Blended learning was not associated with reduced quality of life or increased mental health symptoms compared to in-person learning among children and adolescents and should be considered as a viable alternative to in-person learning.